2015
DOI: 10.1017/sjp.2015.45
|View full text |Cite
|
Sign up to set email alerts
|

Sharing in Private and Public Situations: does this really Matter for Children?

Abstract: The goal of the present study was to examine the influence of social context in young children's sharing behavior. Sixty-three children, aged between 3 and 8 years, participated in a dictator game in which they were requested to distribute stickers between themselves and an anonymous child. Results showed that the quantities the participants expected to receive were greater than those which were distributed to the others, t(63) = -6, 28, p < .01. Moreover, older participants shared more stickers when they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
1
8
0
3
Order By: Relevance
“…However, the results of the study by Smith et al (2013) indicated no relationship between inhibitory control and sharing behavior between 3 and 8 years of age. This may have been due to a strong social desirability bias, as shown in previous studies, in which it was found that children of this age group tend to behave more fairly and equitably when being observed than when alone (Blake & Rand, 2010;Piazza et al, 2011;Sampaio & Pires, 2015).…”
Section: Palabras Clave: Desarrollo Moral Infancia Autocontrolmentioning
confidence: 71%
See 4 more Smart Citations
“…However, the results of the study by Smith et al (2013) indicated no relationship between inhibitory control and sharing behavior between 3 and 8 years of age. This may have been due to a strong social desirability bias, as shown in previous studies, in which it was found that children of this age group tend to behave more fairly and equitably when being observed than when alone (Blake & Rand, 2010;Piazza et al, 2011;Sampaio & Pires, 2015).…”
Section: Palabras Clave: Desarrollo Moral Infancia Autocontrolmentioning
confidence: 71%
“…Finally, a regression analysis was performed to assess the predictive value of age and hits in Stroop on the number of stickers donated (Table 2), considering the results of previous studies regarding the following aspects: (a) increased sharing in agerelated economic games situations (Blake & McAuliffe, 2011;McAuliffe et al, 2014;Sampaio & Pires, 2015;Smith et al, 2013); (b) the role that inhibitory control plays in delaying gratifications (Kidd et al, 2013), thus contributing to increased altruistic behaviors (Aguilar-Pardo et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations